Fast Lithium Ion Migration in Room Temperature LiBH4 - Lee, Young-Su; Cho, Young Whan (American Chemical Society, 2017)
The defect structure and the Li ion diffusion mechanism of orthorhombic LiBH4 (o-LiBH4) are studied by first-principles calculations to elucidate the Li ion transport in o-LiBH4. Two metastable Li interstitial sites are identified, and the formation energies of the Schottky and Frenkel defect pair are calculated to be 1.2-1.4 eV, the former being slightly easier to form. The energy required to form intrinsic defects is higher than that of hexagonal LiBH4 (h-LiBH4). On the other hand, the migration energy barrier of the Li vacancy or interstitial ranges from 0.1 to 0.3 eV, which is comparable to that of hLiBH(4). Therefore, the higher defect formation energy mainly accounts for the much lower Li ion conductivity of o-LiBH4. The calculated overall activation barrier for the Li ion conduction in fair agreement with the experimental activation energy. Molecular,dynamics simulation demonstrates that both the interstitial and the interstitialcy mechanisms are operative for the Li interstitial diffusion and that the interconnected interstitial sites compose a fast diffusion path. The simulation results point out that the enhancement of the carrier density via defect or interface engineering may significantly raise the ionic conductivity of o-LiBH4.
Keywords: TOTAL-ENERGY CALCULATIONS; WAVE BASIS-SET; NANOCONFINED LIBH4; SUPERIONIC CONDUCTIVITY; SOLID ELECTROLYTES; BATTERIES; STORAGE; LICE(BH4)(3)CL; EFFICIENCY; LI2B12H12